Glycosaminoglycans: Participants in Microvascular Coagulation of Sepsis - Li, Nanxi; Hao, Ruolin; Ren, Peng; Wang, Jingya; Dong, Jiahui; Ye, Tong; Zhao, Danyang; Qiao, Xuan; Meng, Zhiyun; Gan, Hui; Liu, Shuchen; Sun, Yunbo; Dou, Guifang; Gu, Ruolan (Thrombosis and Haemostasis, 2024)
Sepsis represents a syndromic response to infection and frequently acts as a common pathway leading to fatality in the context of various infectious diseases globally. The pathology of severe sepsis is marked by an excess of inflammation and activated coagulation. A substantial contributor to mortality in sepsis patients is widespread microvascular thrombosis-induced organ dysfunction. Multiple lines of evidence support the notion that sepsis induces endothelial damage, leading to the release of glycosaminoglycans, potentially causing microvascular dysfunction. This review aims to initially elucidate the relationship among endothelial damage, excessive inflammation, and thrombosis in sepsis. Following this, we present a summary of the involvement of glycosaminoglycans in coagulation, elucidating interactions among glycosaminoglycans, platelets, and inflammatory cells. In this section, we also introduce a reasoned generalization of potential signal pathways wherein glycosaminoglycans play a role in clotting. Finally, we discuss current methods for detecting microvascular conditions in sepsis patients from the perspective of glycosaminoglycans. In conclusion, it is imperative to pay closer attention to the role of glycosaminoglycans in the mechanism of microvascular thrombosis in sepsis. Dynamically assessing glycosaminoglycan levels in patients may aid in predicting microvascular conditions, enabling the monitoring of disease progression, adjustment of clinical treatment schemes, and mitigation of both acute and long-term adverse outcomes associated with sepsis.
Keywords: sepsis; glycosaminoglycans; thrombosis; inflammation; detection methods